Implementation of functional and semi-functional additives in modern food industry technologies - Sviatnenko, Roman; Shubina, Yevgenia; Ianchyk, Mariia (My University, 2025)
The work examines modern approaches to the introduction of functional and semi-functional additives in food technology in the context of the development of healthy and personalized nutrition. The use of dietary fibers, probiotics, antioxidants, protein-hydrocolloid compositions and plant raw materials and their influence on the nutritional and technological value of products were analyzed. It has been shown that the use of functional ingredients improves the organoleptic and structural-mechanical properties of products, increases their stability and helps to extend the shelf life. A conclusion was made about the prospects of using functional additives to create competitive and safe food products with given health-improving properties. У роботі розглянуто сучасні підходи до впровадження функціональних і напів функціональних добавок у технології харчових продуктів у контексті розвитку здорового та персоналізованого харчування. Проаналізовано використання харчових волокон, пробіотиків, антиоксидантів, білково-гідроколоїдних композицій і рослинної сировини та їх вплив на харчову й технологічну цінність продукції. Показано, що застосування функціональних інгредієнтів покращує органолептичні та структурно-механічні властивості продуктів, підвищує їх стабільність і сприяє подовженню терміну зберігання. Зроблено висновок про перспективність використання функціональних добавок для створення конкурентоспроможних і безпечних харчових продуктів із заданими оздоровчими властивостями.
Keywords: кафедра експертизи харчових продуктів; кафедра технології м’яса і м’ясних продуктів; functional products; функціональні продукти